Study and Analysis of Texts Using Indian Literary Theories (International Journal of Food and Nutritional Sciences, 2023)
This paper explores Indian literary theories, focusing on key concepts such as rasa (aesthetic experience), dhvani (suggestion), alankara (ornamentation in poetry), and kavya (artistic poetry), and their impact on both classical and modern literature. Beginning with the foundational concepts in Bharata Muni’s Natyashastra and Anandavardhana's Dhvanyaloka, the paper examines how these theories shape the emotional and intellectual experiences of audiences in various literary forms, including Sanskrit literature, Tamil poetry, and modern Indian cinema. The paper highlights the continuing relevance of Indian aesthetic theories in contemporary literature and global literary criticism, emphasizing their contributions to postcolonial and diaspora studies. The reinterpretation of these classical theories in modern contexts, including their application to narrative forms and cinematic storytelling, demonstrates the flexibility and depth of Indian literary traditions. Challenges such as the dominance of Western literary frameworks and the commercialization of literature are discussed, alongside opportunities for preserving and promoting Indian aesthetic traditions in academic and creative spheres. The future of Indian literary theories lies in their capacity to adapt to contemporary forms while retaining their emotional and philosophical core.